Trauma through cognitive lenses: Disrupted time and memory in slaughterhouse-five - Khalaf, Bilal K; Al-Abbas, Linda S; Hasan, Sarah N; Alqaryouti, Marwan H; Alali, Omar M (Research Journal in Advanced Humanities, 2026)
This study intends to assess Slaughterhouse-Five using Mental Spaces Theory, finding out how the war trauma disturbs our understanding of time and memory. It investigates how Billy Pilgrim’s involvements of existence ‘unstuck in time’ characterize the psychological properties of war. In merging trauma, cognitive linguistics and literary studies, the study expands multidisciplinary practices for examining combat tales. It drives beyond symbolic or historical readings of Slaughterhouse-Five, emphasizing the descriptive power of Mental Spaces Theory in understanding narrative ruin. A hybrid textual analysis utilised on Fauconnier’s Mental Spaces Theory and trauma theory. Significant instants including time shifts, memory loops, and mythical places such as Tralfamadore are thematically investigated as created mental concepts that help the protagonist traverse terrible trials. The findings indicated chronicle tendencies which identified to determine the cognitive reform of time and memory in the scenery of trauma. Accordingly, the scrappy timeline in Slaughterhouse-Five allows the mind to deal with unpleasant experiences. The theory enables past, present, and potential futures’ coexistence, representing the nonlinear nature of traumatic memory recollection. Further implications are identified for policymakers and translation education through understanding trauma tales as mental operations more willingly than narrative deviations.